ANALYSIS OF BOTTOM GILLNET FISHING AND DEVELOPMENT IN DUMAI CITY - Winarti, Lilis; Zain, Jonny; Syofyan, Irwandy (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
The research was conducted on January 2016 at Pangkalan Pendaratan Ikan (PPI) Dumai City with the aim of the research is to prepare the development direction of gillnet fishing effort undertaken by the fisherman at Dumai city by using survey methods. The results showed that the bottom gillnet business as a feasible alternative fishing gear in terms of availability of raw materials, labor availability, market opportunities and business interests with an average value of 3,67. Financially feasible to be developed at an investment cost incurred on average Rp 93.122.400. BCR value of 1,45 to the value of FRR is 32,00 % higher than the bank rate of 7,25% applies. PPC value (payback period of capital) is 3,28 year. Bottom gillnet can be maintained and developed to improve the fishing vessel, the addition of fishing gear, provision of navigational tools as well as cold storage. After a review of the feasibility aspects of business development and financial analysis.Keywords : Bottom gillnet, Feasibility, Financial Analysis, PPI Dumai